Implementación de un sistema de automatización para la clasificación y cuantificación de leche enfundada en la empresa láctea INLADEC provincia de Cotopaxi cantón Salcedo. - Córdova Guaraca, Marco Vinicio (2020)
The dairy company INLADEC is located in the province of Cotopaxi, Canton of Salcedo. This company dedicated to the elaboration of dairy products (milk, yogurt, and cheese), most of the processes used in the production are not automated, so the staff performs the tasks of manually classification and quantification, by this reason there are errors when counting and classifying milk covers, and this causes economic losses to the company. In this sense, the automation system that will be implemented to classify the product in the conveyor belt, it bases on the implementation of a profile held by two supports. These will divide the belt into two sections; for section A the ½ L covers are found, and for section, B is the 1L covers after making the classification. The covers will be transported to a sensor where it will count the number of milk covers that exist in each batch. It sends the signal to a programmable logic controller counter to activate the solenoid valves that will actuate the pneumatic actuators, which fulfill the function of an automatic gate to allow the number of covers needed for each batch of milk to pass, this process repeated after each batch completed. This automation contributes to this company economically, optimizing the time in the production processes, due to these the errors produced by counting and manual sorting will be eliminated.